Arduino – Based Electronic Voting Machine - Marwa Adeeb Al-jawaherry (Tikrit Journal of Pure Science)
The main objective of this paper is to design and implement Electronic Voting Machine (EVM) using fingerprint sensor for authentication. The design is based on the microcontroller (Arduino Mega 2560), fingerprint sensor for scanning voter’s fingerprint before voting, “2.4” TFT LCD screen for displaying the instructions and voter information, Buzzer, SD card reader. System database comprising password ID for all voters and fingerprint are stored in microcontroller for comparing and verification during polling. If already voter casted his vote and he/she trying to enter for second time into the electronic voting machine, then buzzer will alert the master user. The proposed Electronic Voting Machine will save the time and effort of voters as it is characterized by reliability and ease of use in addition to rapid response to users. At the end of the ballot, the result will be stored in flash memory through which the master user can retrieve and see them. During the construction of any electronic voting system, several aspects must consider, the most important is the privacy of voters and the accuracy of the voting process in addition to maintaining the security of data, this research provides a safe and reliable voting system.